2014
DOI: 10.1074/jbc.m113.515791
|View full text |Cite
|
Sign up to set email alerts
|

Arresting a Torsin ATPase Reshapes the Endoplasmic Reticulum

Abstract: Background:TorsinB is an AAAϩ ATPase of unknown function. Results: ATPase-arrested TorsinB induces the formation of LULL1-enriched, luminally constricted ER membranes requiring a highly conserved C-terminal motif in TorsinB. Conclusion: Membrane structures formed by the TorsinB dominant-negative mutant are dependent on association with ATPase-activating factor LULL1. Significance: This study supports a role for TorsinB in membrane dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 39 publications
6
50
0
Order By: Relevance
“…We further showed that this equivalent Torsin-activator interface exists with LULL1 as well (Fig. 3E), consistent with our previous data for LULL1 and TorB (24). All in all, these cross-linking experiments faithfully recapitulate the previously established nucleotide dependency of the cofactor interaction, as well as its disruption by the ΔE mutation (3,4,21).…”
Section: Significancesupporting
confidence: 91%
See 3 more Smart Citations
“…We further showed that this equivalent Torsin-activator interface exists with LULL1 as well (Fig. 3E), consistent with our previous data for LULL1 and TorB (24). All in all, these cross-linking experiments faithfully recapitulate the previously established nucleotide dependency of the cofactor interaction, as well as its disruption by the ΔE mutation (3,4,21).…”
Section: Significancesupporting
confidence: 91%
“…3 C-E and Fig. S5) and is in excellent agreement with all previously published mutagenesis and activity data (24)…”
Section: Significancesupporting
confidence: 91%
See 2 more Smart Citations
“…For transient expression, plasmids were transfected into HEK 293T cells using Lipofectamine TM 2000 (Life Technologies). Experiments were performed 24 h post-transfection as described previously (20), unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%